2003
DOI: 10.1111/j.1750-3639.2003.tb00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Expression of Sodium‐dependent Glutamate Transporters and Synthetase: a Neuroprotective Role for Activated Microglia and Macrophages in HIV Infection?

Abstract: It is now widely accepted that neuronal damage in HIV infection results mainly from microglial activation and involves apoptosis, oxidative stress and glutamate-mediated neurotoxicity. Glutamate toxicity acts via 2 distinct pathways: an excitotoxic one in which glutamate receptors are hyperactivated, and an oxidative one in which cystine uptake is inhibited, resulting in glutathione depletion and oxidative stress. A number of studies show that astrocytes normally take up glutamate, keeping extracellular glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 100 publications
(170 reference statements)
0
40
0
Order By: Relevance
“…Furthermore, Glu is not only an excitatory neurotransmitter in the central nervous system but also a metabolic substrate. The intracellular Glu pool has been implicated as a source of direct synthesis of glutathione in preclinical studies (45), in which, in the early stage of HIV infection, activation of glutathione synthesis, which requires Glu as substrate, has been reported (19,38). To our knowledge, this is the first report of measurements of uncontaminated Glu concentrations in the frontal WM and posterior cingulate gyrus brain regions of HIV-seropositive patients, using a reliable method to separate Glu from Gln (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, Glu is not only an excitatory neurotransmitter in the central nervous system but also a metabolic substrate. The intracellular Glu pool has been implicated as a source of direct synthesis of glutathione in preclinical studies (45), in which, in the early stage of HIV infection, activation of glutathione synthesis, which requires Glu as substrate, has been reported (19,38). To our knowledge, this is the first report of measurements of uncontaminated Glu concentrations in the frontal WM and posterior cingulate gyrus brain regions of HIV-seropositive patients, using a reliable method to separate Glu from Gln (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…They express TNF-α, IL (interleukin)-1, IFN-α (interferon)-α and NOS [NO (nitric oxide) synthase], among other inflammatory mediators [52,53]. It should be noted, however, that recent work has shown that these cells may have neuroprotective properties, especially early in the infection [54,55], suggesting that the immune response has a desired effect initially and does not become damaging until the infection becomes chronic.…”
Section: Activated Macrophages and Microgliamentioning
confidence: 97%
“…These transporters maintain basal levels of extracellular glutamate in the range of 1-2 lM and thus prevent overactivation of GluRs under physiological conditions. Interestingly, activated microglia and brain invading macrophages also express glutamate transporters after mechanical stimulation (van Landeghem et al, 2001) and HIV-induced CNS damage (reviewed by Gras et al, 2003) (Table 2).…”
Section: Glutamate Signaling In Glial Cellsmentioning
confidence: 98%